A prospective intra-individual evaluation of silk compared to Biobrane for the treatment of superficial burns of the hand and face. Issue 3 (May 2017) - Schiefer, Jennifer Lynn; Arens, Elena; Grigutsch, Daniel; Rath, Rebekka; Hoffmann, Alexandra; Fuchs, Paul Christian; Schulz, Alexandra
Highlights: First report evaluating silk compared to Biobrane on 2a burn wounds. First report evaluation natural silk for the treatment of hands and face. First intra-individual study comparing Biobrane and silk. Abstract: Introduction: An ever-increasing number of commercially available dressings have been applied to treat superficial burns with the aim to reduce pain and inflammation and lead to a fast wound healing and scar reduction. Nevertheless the search for cheap and effective wound dressing proceeds. Dressilk ® consisting of silkworm silk showed good results for wound healing in regards to scarring, biocompatibility and reduction of inflammation and pain. Therefore it seemed to be an interesting product for the treatment of superficial burns. Methods: In a prospective intra-individual study the healing of superficial burns was evaluated after the treatment with Dressilk ® and Biobrane ® in 30 patients with burns of the hand and face. During wound healing pain, active bleeding, exudation, dressing change and inflammation were evaluated using the Verbal Rating Scale 1–10. Three months later scar appearance was assessed by VSS (Vancouver Scar Scale) and POSAS (Patient and Observer Scar Scale). Results: With regard to re-epithelialization, pain, inflammation and acute bleeding both dressings were equivalent. High subjective satisfaction rates were reported for both Dressilk ® and Biobrane ® dressings in regard to comfort and mobility of the face. Biobrane ®, applied as a glove was subjectively preferred for burns of the hand. Regarding their cost efficiency Dressilk ® was clearly superior to Biobrane ® . Long-term results were similar. Conclusion: The "ideal" wound dressing maximizes patients' comfort while reducing pain and promoting wound healing. Dressilk ® and Biobrane ® both provided an effective and safe healing environment, showing low overall complication rates with respect to infection and exudation on superficial burns of the hand and face. Therefore Dressilk ®, being clearly superior to Biobrane ® in cost efficiency is an interesting alternative especially for the treatment of superficial burns of faces.